PENGARUH PENGGUNAAN MEDIA INTERAKTIF FLASH BERBASIS WEB TERHADAP PRESTASI BELAJAR BAHASA INGGRIS KELAS IV - Budiatman, Ino; Ronaningsih, Asih; Pertiwi, Dara (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aimed to investigate the influences of interactive instructional media with Flash web-based on student achievement in learning English. This study used Quasi experiment with a Control Group Design. The research population is SDIT Qonita Islamic School at fourth grade and the sample was taken for 30 students using total sampling technique. Data was collected by using multiple-choice test with 4 alternative answers. Before data collection, this instrument was validated by using r product moment test. The research findings showed a significant influence in the use of interactive instructional media with Flash web-based on student achievement in learning English at SDIT Qonita Islamic School, with an average value of the control group 72.80 and an average value of the experimental group 80.07. Therefore it is suggested to use this instructional media to increase student achievement in learning English.